Achievement Motivation towards Social Studies on Students’ Academic Achievement in Tertiary Institutions in Cross River State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2022)
This research examined Achievement motivation towards Social Studies on students’ academic achievement in tertiary institutions in Cross River State, Nigeria. To achieve the purpose of this study, one hypothesis was formulated to direct the study. Ex-post facto research design was adopted for the study. A sample of six hundred and seventy-three (673) students was randomly selected for the study. The instruments for data collection were the Achievement Motivation towards social Studies Questionnaire (AMTOSSQ) and Social Studies Achievement Test (SOSAT) developed by the researchers which were subjected to validation by experts in measurement and evaluation and psychology. The reliability estimates of the instruments were established through the split-half reliability method and it associate Spearman Brown prophesy formula. Pearson product moment correlation analysis was adopted to test the hypothesis at .05 level of significance. The result of the analysis revealed that achievement motivation towards Social Studies on students’ academic achievement has a significant positive relationship in the subject. Based on the finding of the study, it was recommended that students should develop high achievement motivation towards social studies and other subjects as this will manifest in higher academic achievement and vice versa.
Keywords: Academic Achievement; Achievement Motivation; Social Studies; Students